1999
DOI: 10.1021/ma981457k
|View full text |Cite
|
Sign up to set email alerts
|

Ambidextrous Surfactants for Water-Dispersible Polymer Powders from Dispersion Polymerization in Supercritical CO2

Abstract: A new concept is introduced in which a surfactant, poly(dimethylsiloxane)-b-poly(methacrylic acid) (PDMS-b-PMA) (Mw ) 5500 g/mol PDMS, 900 g/mol PMA), is utilized to stabilize an organic latex in either a nonpolar medium, dense CO2, or water. The latex particles, in this case poly(methyl methacrylate) (PMMA), were synthesized by dispersion polymerization in supercritical carbon dioxide. In CO2, the PDMS block provides steric stabilization while the PMA block adsorbs to the particle surface. Upon transfer to wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 26 publications
0
67
0
2
Order By: Relevance
“…In addition, the particles are much less agglomerated, on the basis of much lower sedimentation rates during polymerization and the SEM images. Previous work has shown that the monomer, methyl methacrylate, enhances steric stabilization, which is lost as the monomer is consumed (15,16). By adding a relatively unreactive cosolvent, it is possible to stabilize the reaction to completion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the particles are much less agglomerated, on the basis of much lower sedimentation rates during polymerization and the SEM images. Previous work has shown that the monomer, methyl methacrylate, enhances steric stabilization, which is lost as the monomer is consumed (15,16). By adding a relatively unreactive cosolvent, it is possible to stabilize the reaction to completion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PDMS-based surfactants have been used to stabilize latexes formed during heterogeneous polymerization of methyl methacrylate (14-16) and styrene (17) in supercritical CO 2 . At low conversions, where monomer acts as a cosolvent, the latexes are stable, but become unstable at high conversions, indicating limitations in the solvation of PDMS by pure CO 2 (15,16). This instability, which is not predicted by simulation studies of symmetric systems, warrants further study.…”
Section: Introductionmentioning
confidence: 93%
“…A new concept for the preparation of water-dispersible polymer particles in CO 2 has been developed by Johnston [34]. PMMA was synthesized in CO 2 using an "ambidextrous" surfactant.…”
Section: Dispersion Polymersmentioning
confidence: 99%
“…thick) perpendicular to the axis with 180 o separation so that UV-Vis spectra of the cell contents could be collected. 19 Another cell was equipped with three 5/8 in. sapphire windows mounted perpendicular to the cell axis with 90 o separation enabling collection of steady state emission and lifetime data.…”
Section: Concentrated Solution Of Contaminantmentioning
confidence: 99%